OP0134 MACROPHAGES SKEWED BY GM-CSF PRODUCE YKL-40, INSTIGATING ANGIOGENESIS IN GIANT CELL ARTERITIS. (2nd June 2020) - Van Sleen, Y.; Jiemy, W. F.; Pringle, S. A.; Abdulahad, W.; Van der Geest, K.; Sandovici, M.; Heeringa, P.; Brouwer, E.; Boots, A.
Abstract : Background: Giant cell arteritis (GCA) is an inflammatory disease affecting the medium- and large-sized arteries. The pathology of GCA is characterized by an infiltrate of mainly CD4+ T-cells and macrophages. These macrophages release a wide range of inflammatory, tissue destructive and proangiogenic proteins, including YKL-40. Previously, we demonstrated that macrophage populations in the vessel wall of GCA patients are heterogeneous; one such macrophage subset highly expressed CD206 and MMP-9, and was located in or near the media layer. Cancer studies have implicated YKL-40 production by tumor-associated macrophages in various inflammatory and tissue remodeling processes, including angiogenesis. Less is known about the role of YKL-40 in inflammatory diseases such as GCA. Objectives: Our objective was to investigate the cellular source and the pro-angiogenic function of YKL-40 in GCA patients. Methods: For this study we performed immunohistochemistry (IHC) and cell culture experiments. IHC for YKL-40 and CD206 was performed on GCA positive temporal artery biopsies (TABs; n=12) and GCA positive aortas (n=10) of treatment-naive patients. Expression of YKL-40 by macrophages was confirmed by double staining with macrophage transcription factor PU.1. Additionally, the TABs were stained for IL-13Rα2, recently described as the receptor for YKL-40. The effect of skewing signals on YKL-40 production was assessed by cell culture of monocyte-derived macrophages of GCA patients with either M-CSF or GM-CSF (n=8). Subsequently, the supernatant was assayed by ELISA. Finally, the angiogenic potential of YKL-40 was investigated by tube formation experiments using human microvascular endothelial cells (HMVECs). Results: YKL-40 is produced by a distinct subset of macrophages in GCA TABs and aortas, usually located in or near the media (Figure 1 shows representative stainings in consecutive slides of a GCA TAB). We here show YKL-40 to be expressed by CD206+/MMP-9+ macrophages in all GCA TABs and aortas. In vitro, macrophages were found to produce YKL-40 (Figure 2 shows an increasing YKL-40 production during the maturation of monocytes towards macrophages over 8 days of culture). GM-CSF stimulation, which is known to upregulate CD206 expression in macrophages, gave rise to higher YKL-40 production by GCA macrophages, when compared to M-CSF stimulated macrophages from GCA patients (p=0.038). In addition, YKL-40 stimulation of HMVECs induced more tube formation compared to unstimulated HMVECs. Finally, we showed, by IHC, abundant expression of the YKL-40 receptor IL-13Rα2 in TABs of GCA patients. Conclusion: Taken together, we show here that a distinct subset of macrophages, skewed by GM-CSF and highly positive for CD206, is responsible for the production of YKL-40 in GCA. The results are in line with previous reports demonstrating that CD206 expression distinguishes YKL-40 positive macrophages from YKL-40 negative macrophages (1). Thus, YKL-40 production by CD206+ macrophages may be involved in angiogenesis in GCA tissues, a process important for the continuation of the inflammatory process. References: [1]Bonneh-Barkay, D. et al., 2012. Astrocyte and macrophage regulation of YKL-40 expression and cellular response in neuroinflammation. Brain Path. 22: 530-546 Disclosure of Interests: Yannick van Sleen: None declared, William Febry Jiemy: None declared, Sarah A. Pringle: None declared, Wayel Abdulahad: None declared, Kornelis van der Geest Speakers bureau: Roche (2019), Maria Sandovici: None declared, Peter Heeringa: None declared, Elisabeth Brouwer Consultant of: Roche (consultancy fee 2017 and 2018 paid to the UMCG), Speakers bureau: Roche (2017 and 2018 paid to the UMCG), Annemieke Boots Consultant of: Grünenthal Gmbh until 2017